Natural Gas Technology - Evaluation of Underground Gas-Storage Conditions In Aquifers Through Investigations of Groundwater Hydrology - P. A. Witherspoon; T. D. Mueller; R. W. Donovan (The American Institute of Mining, Metallurgical, and Petroleum Engineers)
The use of petroleum-barren aquifers for underground storage has become extremely important to the natural-gas industry. A critical problem in assessing the feasibility of a specific aquifer for such use is the permeability determination of the caprock over the proposed storage project. The approach used here is to conduct both static and dynamic field tests on the aquifer being analyzed. Valuable information on the possibility of communication between the storage aquifer and any other aquifers above can be obtained by measuring hydrostatic water levels and water analyses. Significant differences in such data give evidence of the lack of communication between the intended storage reservoir and other horizons. The dynamic approach requires that one well be pumped in the storage aquifer, and changes in fluid levels recorded in both the aquifer and its caprock. The interpretation of the data from such pumping tests involves the solution of nonsteady radial flow in an infinite aquifer and the influence on such flow of a leaky caprock. A finite-difference model has been used to investigate this problem, and the transient behavior has been solved numerically with a digital computer. It has been found that the pressure transients in the storage aquifer are not affected significantly by moderate caprock leakage. The pressure behavior of the caprock is a much better indicator of the degree of leakage, and generalized solutions for this behavior are included. Field data are presented to demonstrate both the static and dynamic approach. If is concluded that appropriate investigation of the groundwater hydrology in an aquifer-type gas-storage project can provide much valuable information for determining the effectiveness of the caprock to hold gas. INTRODUCTION Underground storage of natural gas in the United States has been developing at a rapid rate over the past few years. In 1955, the total gas-storage capacity was about 1.6 trillion cu ft; by 1961, this figure was almost 3.2 trillion cu ft, an increase of 100 per cent in six years.' This trend un- doubtedly will continue because the economics favor the development of gas storage, as opposed to the construction of new pipelines, to meet the inherent cyclic demand for fuel in the metropolitan areas of this country.' About 15 per cent of the current underground gas storage has been developed in petroleum-barren aquifers, i.e., geological domes or anticlines in which no commercial quantities of oil or gas had been produced prior to the storage operations. The necessity for using barren aquifers outside many metropolitan areas of this country has been due to the lack of depleted oil or gas fields that were near enough and large enough to meet the demands of such consuming areas. Pipeline companies have developed aquifer storage along their transmission lines to meet the fluctuating needs of their complex systems. Considerable thought has also been given to the problem of storing gas in a structureless aquifer, both in this country' and in the Soviet Union outside the city of Leningrad.'," Conditions such as these have led to the development of aquifer gas-storage projects in many parts of the U. S. Most of these developments have centered in the Mid-Continent area, and the greatest amount of activity has been concentrated in Illinois.6 Thus, the use of petroleum-barren aquifers for gas-storage purposes has become extremely important to the natural-gas industry. There are three basic problems in developing aquifer-type storage: (1) finding an adequate geologic structure, (2) finding a suitable storage reservoir within the structure and (3) determining the tightness of the caprock over the intended storage zone. The first two problems can be solved by applying conventional methods of exploration geology, but once these problems are solved, the question arises as to why no oil or gas is present in an otherwise favorable setting. Two situations are possible: (1) an adequate source bed was never present, or (2) a source bed was present but the petroleum seeped away because of a leaky caprock. Determining the tightness of the caprock is one of the most critical problems in assessing the feasibility of a specific aquifer for storage purposes. In attacking this problem, one usually takes cores of the caprock and subjects them to a rigorous investigation. Such core data are desirable, but they only detail the matrix properties and cannot be expected to reveal the gross characteristics of the caprock. Several gas-storage projects in the U. S. have had considerable leakage where